Impact of temperature and surfactant addition on milk foams. (June 2021) - Dandigunta, Babuji; Karthick, Arun; Chattopadhyay, Pradipta; Dhoble, Abhishek S.
Abstract: Milk is a complex colloidal solution. Knowledge of milk composition assay is essential for better applications in the dairy industry apart from processing and storage. Several techniques are reported in literature, but their applications are limited due to chemical entailment, invasive nature, and complicated procedures. The present work investigates the possibility of using milk foam properties as composition markers of milk. Surfactants play a key role in generating foams. In the present work, the effect of surfactants and temperature on foams produced from milk of different fat composition was investigated. Temperature effects and the impact of cationic, anionic, and non-ionic surfactants on foams produced from three milk types (cow milk, toned milk, and full cream milk) were studied. Toned milk added with an anionic surfactant sodium dodecyl sulphate (SDS) at 60 °C showed comparatively higher foamability of 122.4 mL. Among pure milk samples, toned milk showed a comparatively higher foamability of 114.65 mL. Cationic surfactant cetyltrimethylammonium bromide (CTAB) showed better milk foaming properties. Tween 80, a non-ionic surfactant showed a minimal or neutral effect on foam properties of milk. The results attained could lay the foundations for developing a novel milk assay protocol with the use of surfactant foams and thermal pre-treatments. Graphical abstract: Image 1 Highlights: Milk foam properties indicative of composition markers of milk. Each surfactant affected the foam properties of milk distinctively. Heating of milk improved foaming qualitatively and quantitatively. SDS was found to improve the foaming properties of milk.